Bilingual Big Book with Integrated SDGs Content to Enhance Reading Skills and Understanding of Sustainable Development Values among Upper Elementary Students - Ni Wayan Surya Mahayanti; Putu Kerti Nitiasih; Ni Luh Era Adnyayanti; I Nyoman Adi Jaya Putra; Jiang Li; Luh Putu Dian Kresnawati (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2026)
Background: English learning that focuses solely on language structure tends to be less engaging, monotonous, and lacking contextual relevance for elementary students. On the other hand, integrating the values of the Sustainable Development Goals (SDGs) into basic education is increasingly essential to foster global awareness, empathy, and social responsibility from an early age. This research aims to develop a Bilingual Big Book that integrates SDG content into bilingual (Indonesian English) stories for use in elementary English learning. The media is expected to improve vocabulary acquisition, reading comprehension, and students' understanding of global sustainability values. Methodology: The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: (1) needs analysis, (2) planning and media design, (3) development and expert validation, (4) limited trial implementation, and (5) evaluation and revision. This study recruited 32 students and 3 English teachers as the participants. Data were collected through pre- and post-tests, teacher and student perception questionnaires, classroom observations, and in-depth interviews. The data were analyzed both quantitatively and qualitatively, utilizing descriptive statistical and the Miles and Huberman interactive model for qualitative interpretation. Findings: The findings revealed that the Bilingual Big Book based on storytelling effectively increased students' interest and engagement in learning English. Quantitatively, there was a significant improved in students' reading comprehension by 28% after using the media and an increase of 31% in thematic vocabulary mastery. In addition, the questionnaire results indicated that 92% of students felt the learning process was more enjoyable and easier to understand, while 87% of teachers stated that the media helped explain language concepts more contextually and also awareness on SDGs values. Conclusion: Overall, this research contributes to the development of adaptive, contextual, and transformative English learning media, while also promoting the implementation of education oriented toward sustainable development and global awareness. The developed media not only enhances students' language proficiency but also cultivates their character to become empathetic, and environmentally conscious individuals. Originality: Previous studies on Big Books emphasized linguistic or character aspects but rarely integrated SDGs as moral and contextual frameworks. This study fills that gap by creating a bilingual storytelling medium that bridges language learning with global citizenship education, offering a novel model for sustainable literacy in elementary classrooms.